2015
DOI: 10.1017/jfm.2015.57
|View full text |Cite
|
Sign up to set email alerts
|

Lift and thrust generation by a butterfly-like flapping wing–body model: immersed boundary–lattice Boltzmann simulations

Abstract: The flapping flight of tiny insects such as flies or larger insects like butterflies is of fundamental interest not only in biology itself but also in its practical use for the development of micro air vehicles. It is known that a butterfly flaps downward for generating the lift force and backward for generating the thrust force. In this study, we consider a simple butterfly-like flapping wing-body in which the body is a thin rod and the rectangular rigid wings flap in a simple motion. We investigate lift and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 50 publications
4
82
0
Order By: Relevance
“…Suzuki and Inamuro (2011) proposed the LBM combined with the multi direct forcing method proposed by Wang et al (2008) (hereafter called multi direct forcing-lattice Boltzmann method, MDF-LBM) which can reduce the error from the no-slip boundary condition by calculating the body force iteratively, and the method was validated by comparing their results with numerical results of flows around an oscillating circular cylinder by Dütsch et al (1998), with numerical results of the sedimentation of an elliptical cylinder by Xia et al (2009), and with experimental results of the sedimentation of a sphere by ten Cate et al (2002). In addition, Suzuki et al (2015) have shown that the MDF-LBM gives good results in comparison with experimental results of an inclined flat plate in a uniform flow by Taira and Collonius (2009) and flapping wings in a stationary fluid by Dickinson et al (1999).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Suzuki and Inamuro (2011) proposed the LBM combined with the multi direct forcing method proposed by Wang et al (2008) (hereafter called multi direct forcing-lattice Boltzmann method, MDF-LBM) which can reduce the error from the no-slip boundary condition by calculating the body force iteratively, and the method was validated by comparing their results with numerical results of flows around an oscillating circular cylinder by Dütsch et al (1998), with numerical results of the sedimentation of an elliptical cylinder by Xia et al (2009), and with experimental results of the sedimentation of a sphere by ten Cate et al (2002). In addition, Suzuki et al (2015) have shown that the MDF-LBM gives good results in comparison with experimental results of an inclined flat plate in a uniform flow by Taira and Collonius (2009) and flapping wings in a stationary fluid by Dickinson et al (1999).…”
Section: Introductionmentioning
confidence: 80%
“…In order to answer this question, we calculate the Blasius's problem by using the MDF-LBM proposed by Suzuki and Inamuro (2011). Since the MDF-LBM has been validated quite extensively in the previous works by Suzuki and Inamuro (2011), Ota et al (2012), and Suzuki et al (2015), the MDF-LBM should give a reliable result even for the Blasius's problem. In addition, the MDF-LBM without iteration is almost the same as other IB-LBMs which have been commonly used by many researchers, e.g., the Proteus proposed by Feng and Michaelides (2005) and the direct forcing approach proposed by Dupuis et al (2008).…”
Section: Blasius's Problemmentioning
confidence: 99%
“…Following the argument from Guo et al (2002), also developed in (De Rosis et al 2014a, b;Suzuki et al 2015;Wang et al 2015),  i is given by:…”
Section: δXmentioning
confidence: 99%
“…In order to simulate this two-way coupling between the fluid environment and the immersed soft matter, a numerical fluid-structure interaction (FSI) code was developed utilizing an immersed boundary coupling scheme. Previous research has shown that the immersed boundary method (IBM) is an efficient approach to simulate soft matter and biological cells [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ], flapping insect wings [ 31 , 32 , 33 ], harmonic oscillation of thin lamina in fluid [ 34 ] and other FSI problems, such as particle settling [ 35 ]. The advantage of this approach is two-fold.…”
Section: Fluid-structure Interaction Modelmentioning
confidence: 99%